Investigating Some Novel Closed Neighborhood Topological Indices of Nanostructures (Journal of Informatics and Mathematical Sciences, 2025)
Chemical graph theory plays an essential role in mathematical chemistry by representing chemical compounds as molecular graphs and utilizing graph-theoretical methods to analyze them. Topological indices (TIs) are numerical parameters that describe the structure of a molecular graph. In this work, we introduced newly defined seven closed neighborhood topological indices and compute the same for some standard classes of graphs. Later, we examine these indices with some physical properties of octane isomers. Our indices exhibits highly correlation with acentric factor of octane isomers. Additionally we derive the expression for seven TI's of \(TUC_4C_8 (R) [p, q]\) nanostructures as well as subdivision graph and the line graph of the subdivision graph of \(TUC_4C_8 (R) [p, q]\) nanostructures.